If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -2(4 + 5x) = 19 + -2(2x + -2) -3x + (4 * -2 + 5x * -2) = 19 + -2(2x + -2) -3x + (-8 + -10x) = 19 + -2(2x + -2) Reorder the terms: -8 + -3x + -10x = 19 + -2(2x + -2) Combine like terms: -3x + -10x = -13x -8 + -13x = 19 + -2(2x + -2) Reorder the terms: -8 + -13x = 19 + -2(-2 + 2x) -8 + -13x = 19 + (-2 * -2 + 2x * -2) -8 + -13x = 19 + (4 + -4x) Combine like terms: 19 + 4 = 23 -8 + -13x = 23 + -4x Solving -8 + -13x = 23 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -8 + -13x + 4x = 23 + -4x + 4x Combine like terms: -13x + 4x = -9x -8 + -9x = 23 + -4x + 4x Combine like terms: -4x + 4x = 0 -8 + -9x = 23 + 0 -8 + -9x = 23 Add '8' to each side of the equation. -8 + 8 + -9x = 23 + 8 Combine like terms: -8 + 8 = 0 0 + -9x = 23 + 8 -9x = 23 + 8 Combine like terms: 23 + 8 = 31 -9x = 31 Divide each side by '-9'. x = -3.444444444 Simplifying x = -3.444444444
| N-3=16 | | 24+8b=-8(-7+3b) | | 6x4-12/2 | | 4-2(x-3)=19-5 | | 18(1/6b-1/9)=22 | | 8x+4=3x+3 | | 92-6x=8x+2 | | 18(1/6b-1/2)=22 | | 4(3z-7)+3(5z+1)=54 | | -16+v=5(v-8) | | 5x+9=3x+21 | | 4(3z+7)+3(5z+1)=54 | | 12(1/3b+1/2)=18 | | 4(3z+7)+5z+1=54 | | 4(3z-7)+5z+1=54 | | -9x=-7 | | -4(5+2n)=-35-5n | | 2(5x+6)=10x+12 | | .5x^2-16x-5=0 | | 4(2x-7)=6(x+3) | | n+5*2=24 | | 3x+58=6x+21 | | 3(x+2)=25(12x+4)-5x | | -2-7x=-8(2x-1)-x | | 1-(3)+7=7 | | 7x+6=4(x+2)-2 | | 17x+5=12x+20 | | 15=9x-4 | | 1-(3)= | | 1.1x=3.52 | | 19=t/4 | | 14x-42=14x-42 |